2013
DOI: 10.1007/s00382-013-1929-z
|View full text |Cite
|
Sign up to set email alerts
|

How well do the current state-of-the-art CMIP5 models characterise the climatology of the East Asian winter monsoon?

Abstract: Previous studies have revealed some common biases in coupled general circulation model's simulations of the East Asian (EA) winter monsoon (EAWM), including colder surface air temperature and more winter precipitation over the EA region. In this study, we examined 41 fully coupled atmosphere-ocean models from fifth phase of the Coupled Model Intercomparison Project (CMIP5), which will be widely used in the fifth assessment report of the Intergovernmental Panel on Climate Change (IPCC), and address whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…The decadal weakening of EAT is also captured by most of the coupled climate models in IPCC AR4 [19]. Under a global warming scenario, the EAT becomes shallower and shifts northeastward in the coupled climate models [20][21][22][23]. The performances of the models in the Coupled Model Intercomparison Project phase 5 (CMIP5) in simulating EAWM are better than those in CMIP3 [23].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The decadal weakening of EAT is also captured by most of the coupled climate models in IPCC AR4 [19]. Under a global warming scenario, the EAT becomes shallower and shifts northeastward in the coupled climate models [20][21][22][23]. The performances of the models in the Coupled Model Intercomparison Project phase 5 (CMIP5) in simulating EAWM are better than those in CMIP3 [23].…”
Section: Introductionmentioning
confidence: 98%
“…The performances of the models in the Coupled Model Intercomparison Project phase 5 (CMIP5) in simulating EAWM are better than those in CMIP3 [23]. The multimodel ensemble (MME) of CMIP5 models is able to reproduce the overall characteristics of EAWM very well [24,25], although the climatological strength of the EAT is overestimated by most of the models [23,24]. However, the performances of CMIP5 models in the variation of EAT are unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, great progress has been made in the current climate models to have higher resolutions (both horizontal and vertical), more complete physical processes, and more sophisticated parameterization schemes. This has greatly improved model performance and applicability for climate change projections on global to regional scales [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several evaluation studies with focus on the model reproduction of East Asian summer and winter monsoon climate (e.g., Boo et al 2011;Gong et al 2014;Wei and Bao 2012;Wei et al 2014). It was shown that in the winter season, the current state-of-the-art CMIP5 models have the ability to reproduce circulation in EA region and progress had been made to relieve the surface cold bias, which was observed in the CMIP3 model ensemble.…”
Section: Introductionmentioning
confidence: 99%